2009
DOI: 10.1111/j.1471-0528.2009.02348.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors and outcomes associated with the induction of labour in Latin America

Abstract: Objective To describe the prevalence of labour induction, together with its risk factors and outcomes in Latin America.Design Analysis of the 2005 WHO global survey database.Setting Eight selected Latin American countries.Population All women who gave birth during the study period in 120 participating institutions.Methods Bivariate and multivariate analyses.Main outcome measures Indications for labour induction per country, success rate per method, risk factors for induction, and maternal and perinatal outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
82
6
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 39 publications
10
82
6
6
Order By: Relevance
“…Dean Leduce and Jarson Gardosi recorded postdates as highest indication for induction of labor [16,40]. Similarly, frequent indication for induction was postdates observed by Guerra et al [10,26,41] Along with postdates, the hypertensive diseases of pregnancy are many times become the main indications for induction of labor [21]. Whereas…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dean Leduce and Jarson Gardosi recorded postdates as highest indication for induction of labor [16,40]. Similarly, frequent indication for induction was postdates observed by Guerra et al [10,26,41] Along with postdates, the hypertensive diseases of pregnancy are many times become the main indications for induction of labor [21]. Whereas…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sanchez-Ramos et al observed 80% of indications for post-term pregnancies and rest for pregnancy induced hypertension and PROM [42]. Mozurkewich et al and Abdul and Guerra et al reported both postdated and PROM are the common indications for induction with high-quality evidence from various studies, whereas oligohydramnios was found with moderate evidence [26,43]. The induction of labor is commonly indicated in prevention of prolonged pregnancy, prelabor rupture of membranes after 34 weeks, intrauterine fetal death, placental abruption, chorioamnionitis, and hypertensive disorders as stated by NICE and ACOG [44,45].…”
Section: Tripathy and Babymentioning
confidence: 99%
See 1 more Smart Citation
“…The start time of induction was recorded from the first induction intervention of either insertion of prostaglandins or amniotomy. Secondary outcomes were also investigated in the main sample to consider some adverse maternal and neonatal effects which have been associated with induction (Phillip et al, 2004;Guerra et al, 2009). These included postpartum haemorrhage (estimated blood loss of > 500mls) and admission to newborn intensive care.…”
Section: Measurementsmentioning
confidence: 99%
“…There is also a 5% risk of excessive uterine activity, known as tachysystole, which can reduce placental blood flow resulting in fetal heart rate abnormalities and eventual fetal hypoxia if untreated (Thomas et al, 2014). Observational studies have suggested that induction compared with spontaneous labour is associated with increased risk of caesarean delivery (Ehrenthal et al, 2010), postpartum haemorrhage (Phillip et al, 2004), increased admission to newborn intensive care and increased use of analgesia/anaesthetics (Guerra et al, 2009). However, there are concerns that using spontaneous labour as a comparison group may be inappropriate as this is not a choice available for clinicians and may lead to exaggerated estimates by excluding planned caesarean sections (Danilock et al, 2016).…”
Section: Introductionmentioning
confidence: 99%